Environmental dimensionality simplifies biological predictability under complex global change - Peixuan Liu; Bin Huang; Yuan Jia; Junyan Li; Enqi Zhang; Shuming Lin; Zihong Li; Jing Tian; Zijie Wei; Zihan Liu; Mengyao Liang; Runqian Jiang; et al. (Marine Pollution Bulletin, 2026)

Urban sidewalk detection via a cross-view joint segmentation method using satellite and street-view imagery - Yi Lin; Weijia Li; Jinhua Yu; Junyan Ye; Jun He; Xiang Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dysurf: A program for simulating four-dimensional dynamical structure factor - Yongheng Li; Changpeng Lin; Qi Ren; Junyan Liu; Bin Wei; Jiawang Hong (Computer Physics Communications, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Phosphorus availability overrides evolutionary adaptation to warming and high carbon dioxide in shaping diatom physiology and lipid metabolism - Mengcheng Ye; Peixuan Liu; Jiamin Lin; Siyu Luan; Meimei He; Tian Shen; Zexu Li; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; et al. (Limnology and Oceanography, 2026)
Rising ocean temperatures and CO 2 concentrations are reshaping phytoplankton physiology, yet how long‐term adaptation to these stressors interacts with nutrient limitation remains poorly understood. Phosphorus (P) frequently limits phytoplankton growth in coastal and stratified oceans, but it remains unclear whether adaptation to warming and elevated CO 2 modifies responses to P limitation and whether such adaptive advantages can be realized under nutrient stress. Here, we combined multi‐year experimental evolution of the model diatom Phaeodactylum tricornutum under warming, elevated CO 2 , and their combination with short‐term assays across a phosphorus gradient to examine how evolutionary history influences responses to P availability. Across all adaptation regimes, P availability overwhelmingly governed growth, photosynthetic performance, and lipidome structure. Long‐term adaptation increased maximum growth rate and phosphate affinity, but these advantages were largely suppressed under P limitation. Lipidomic analyses revealed extensive P‐driven membrane remodeling, characterized by declines in phospholipids and increases in glycolipids and neutral lipids. While lipid‐class remodeling remained highly conserved across adaptation regimes, structural lipid traits responded differently depending on both evolutionary history and phosphorus status. Under P‐replete conditions, warming and elevated CO 2 primarily promoted fatty‐acid elongation, whereas under P limitation they increased fatty‐acid desaturation. These results demonstrate that nutrient regimes constrain evolutionary responses to warming and elevated CO 2 , highlighting phosphorus as a key determinant of diatom resilience in future oceans. Increasing nutrient limitation in future oceans may therefore restrict the extent to which phytoplankton populations can realize adaptive advantages under climate change, with implications for marine productivity and biogeochemical cycling.

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Pharmacological interventions targeting cognition and related clinical outcomes in vascular dementia: a systematic review and meta-analysis of randomized controlled trials - Tianyu Cheng; Lin Zhang; Yizhou Zhang; Huazheng Liang; Junyan Wang; Gengzhen Chen; Yujia Huo (European Journal of Clinical Pharmacology, 2026)
Purpose Randomized evidence for pharmacological interventions in vascular dementia (VaD) is fragmented. We conducted a VaD-focused, scale-specific systematic review and meta-analysis. Methods We searched four databases for English-language parallel-group randomized controlled trials (1990–2025). Comparable placebo-controlled outcomes were pooled using random-effects meta-analysis; non-poolable outcomes were synthesized according to SWiM. Risk of bias and certainty were assessed with RoB 2 and GRADE. Results Sixteen trials included 5,668 participants across trial cohorts; with one exception, all were published in 2012 or earlier. EGb 761 ® was evaluated in three trials; nimodipine, galantamine, memantine, and rivastigmine in two each; and pentoxifylline, citicoline, sulodexide, donepezil, and Tianzhi granule in one each. Galantamine reduced ADAS-Cog/11 scores (2 trials, n = 1,332; MD − 2.01, 95% CI − 3.18 to − 0.85) and ADAS-Cog/13 scores (2 trials, n = 1,328; MD − 2.51, 95% CI − 3.87 to − 1.15), and memantine reduced ADAS-Cog/11 scores (2 trials, n = 752; MD − 2.20, 95% CI − 3.24 to − 1.15); certainty was moderate. EGb 761 ® reduced SKT scores (3 trials, n = 283; MD − 2.65, 95% CI − 5.17 to − 0.12), but heterogeneity was extreme (I²=92.8%; very low certainty). Galantamine showed no clear NPI benefit (2 trials, n = 1,310; MD − 0.13, 95% CI − 4.05 to 3.79), and memantine showed no clear GBS benefit (2 trials, n = 595; MD − 1.93, 95% CI − 4.69 to 0.84). Evidence for the other seven interventions was mainly single-trial and non-poolable; functional and global outcomes did not establish consistent benefit. Conclusion Galantamine and memantine showed small short-term cognitive effects; EGb 761 ® suggested a fragile, very low-certainty signal; patient-important benefits remain uncertain.

A Musculoskeletal-Finite Element Study of Knee Joint Loading and Cartilage Mechanics in Children with Cerebral Palsy - Dongfei Huo; Run Lin; Junyan Li; Timothy P. Holsgrove; Dominic Farris; Dong Wang; Xijin Hua (Annals of Biomedical Engineering, 2026)
Purpose Cerebral palsy (CP) is typically associated with abnormal gait that may alter knee joint loading and accelerate joint degeneration. We developed an integrated musculoskeletal-finite element (MSK-FE) framework to quantify differences in knee joint biomechanics between children with CP and typically developing (TD) peers. Methods Gait data from 13 children (TD, n = 5; hemiplegia [HP], n = 4; diplegia [DP], n = 4) were analyzed using OpenSim to obtain knee kinematics and compressive knee joint reaction forces (KJRFs). These were applied to scaled 3D FE knee models, incorporating biphasic cartilage, menisci, and ligaments, at the first force peak, mid-stance, and second force peak to evaluate cartilage pressures. Results Compared with TD, both CP subtypes (HP and DP) exhibited greater knee flexion throughout the gait cycle, except for the affected limb in HP (HP A ), which showed reduced flexion during the stance phase. Peak KJRFs over the gait cycle were slightly higher in DP and HP A than in TD, whereas the unaffected limb in HP (HP UA ) generated the highest peak KJRFs among all groups, indicating compensatory overloading of the unaffected limb in HP. Correspondingly, FE analysis showed that peak cartilage contact pressures in the HP cohorts were significantly higher than in DP and TD, while pressures in DP were slightly higher than in TD over the gait cycle. The HP UA showed the highest contact pressures among all groups. Conclusion The MSK-FE framework quantified knee loading and cartilage contact pressure patterns in children with CP. These preliminary findings highlight subtype- and limb-specific gait-loading patterns and provide a mechanistic basis for future larger-scale and longitudinal investigations.

Intelligent mapping of urban scenic view corridors based on public perception: A case study of Chongqing, China - Yuyue Huang; Junyan Yang; Jiewei Zhang; Jingquan Lin; Zhijian Zhou (Applied Geography, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

Rapid evolution of marine phytoplankton under global change: mechanisms, constraints, and ecological consequences - Siyu Luan; Peixuan Liu; Bin Huang; Enqi Zhang; Junyan Li; Shuming Lin; Zihong Li; Tian Shen; Meimei He; Zexu Li; Jianrong Xia; Peng Jin (Marine Environmental Research, 2026)

Atypical tetrahedron of Mn-based hybrid halides inducing narrow pure yellow-light emission - Shiqiang Liu; Zhibin Lin; Junyan Wu; Qiuqin Huang; Qiushui Chen; Qidan Ling; Zhenghuan Lin (Chemical Engineering Journal, 2026)

WD-HRNN-BiGRU: A Novel Spatiotemporal Sequence Multi-Value Prediction Model - Zhongrong Zhang; Junyan Sun; Yulin Shen; Kang Lin; Yijia Liu; Jisheng Li (Water Resources Management, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Dual-network hydrogel loaded with octreotide promotes diabetic wound healing by inhibiting cGAS-STING pathway - Bin Chen; Hang Li; Hong Zhang; Junyan Xu; Shuofu Liang; Ghazal Shokraneh; Hecheng Ma; Gang Wang; Junhao Lin; Zhijian Wei (Chemical Engineering Journal, 2025)

Splicing factor Nova regulates the splice variants in exons 3 and 6 of GABA receptor subunit RDL from Chilo suppressalis Walker (Lepidoptera: Crambidae) - Zijiao Song; Jie Jiang; Tao Tang; Guanghua Luo; Junyan Wang; Kaixiang Lin; Lili Mu; Chunqing Zhao (Pesticide Biochemistry and Physiology, 2025)

Multiscale structural design of heterostructured carbon/boron nitride aerogels for efficient thermal conductivity and broadband electromagnetic wave absorption - Zhengxuan Li; Wang Yang; Chen Zhang; Zhongzhen Ding; Shaoxiong Du; Xi Wu; Junyan Dong; Wenjie Zhu; Sheng Liu; Yu Lin; Lei Liu; Yongfeng Li (Chemical Engineering Journal, 2025)

ETDformer: an effective transformer block for segmentation of intracranial hemorrhage - Wanyuan Gong; Yanmin Luo; Fuxing Yang; Huabiao Zhou; Zhongwei Lin; Chi Cai; Youcao Lin; Junyan Chen (Medical & Biological Engineering & Computing, 2025)

Novel electrolyte design for high-efficiency vanadium redox flow batteries with enhanced 3.0 M V3+ stability at low temperatures - Junyan Du; Huitong Lin; Longyan Zhang; Shiyuan Liu; Lijun Wang (Chemical Engineering Journal, 2025)

Optimizing application strategies of prohexadione-calcium·uniconazole composite regulator to improve lodging resistance and grain yield in rice cultivation in East China - Dengke Ma; Yimin Ding; Yifan Liu; Lin Du; You Mo; Ali Dai; Junyan Xu; Dalu Gu; Liusheng Duan; Weiming Tan (Field Crops Research, 2025)

Outstanding self-healing and plasticity of imine-linked dynamic PDMS with high softness and stability - Fubin Luo; Junyan Sun; Yingbing Zou; Xueyan Yang; Bili Lin; Yixing Feng; Hongzhou Li (Chemical Engineering Journal, 2025)

Combined physiological, biochemical, and multi-omic analyses provide insight into the cause of differential browning in early and late harvested fresh-cut yams - Xi Pang; Zixin Lin; Huafeng Liang; Junyan Shi; Shuzhi Yuan; Xiaozhen Yue; Xiaodi Xu; Yaqi Zhao; Zhifei Wei; Jinhua Zuo; Yuan Sui; Bihong Feng; et al. (Postharvest Biology and Technology, 2025)

Effect of wall slip of CO2-in-water foams on enhanced oil recovery - Biao Xu; Jiuqing Li; Lin Zhu; Junyan Xu; Runze Wang; Shun Li; Jiajia Fu; Jingyi Yang; Tao Liu (Chemical Engineering Journal, 2025)

Papain reduces chilling injury in green bell pepper (Capsicum annuum L.) by regulating the activity and gene expression of antioxidant enzymes - Zixin Lin; Junyan Shi; Hongshan Lu; Yaqi Zhao; Xuanqi Wang; Shuzhi Yuan; Xiaozhen Yue; Xiaodi Xu; Jinhua Zuo; Bin Chen; Bihong Feng; Qing Wang (Postharvest Biology and Technology, 2024)

Organelle synergy unleashed: Modulating mitochondrial-endoplasmic reticulum contacts with a self-assembled prodrug amplifies ferroptosis for innovative cancer therapy - Junyan Zhuang; Renming Fan; Weike Liao; Ruizhuo Lin; Aohua Deng; Ting Zhao; Yongrui Hai; Heran Li; Lei Tang; Gaofei Wei (Chemical Engineering Journal, 2024)

Antiadhesive, antibacterial, and anti-inflammatory sandwich-structured ZIF8-containing gauze for enhanced wound healing - Xinghai Wu; Cheng Wang; Jia Wang; Yuchen Feng; Yunpeng Zhu; Yijia Pan; Yifan Yuan; Chenhui Chen; Junyan Cao; Jixing Lin; Xian Tong; Yuncang Li; et al. (Chemical Engineering Journal, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Identification of SNPs and candidate genes associate with growth performance in all-female mandarin fish (Siniperca chuatsi) by a genome-wide association study - Dingrui Liu; Jin Zhang; Zhenjiang Zou; Chen Long; Jiaqi Lin; Junyan Zeng; Jingpeng Hou; Linqiang Han; Yanlin Jiang; Shuisheng Li; Yong Zhang (Aquaculture, 2024)

The regulation mechanism of hematopoiesis during ischemic and hemolytic anemia in grass carp(Ctenopharyngodon idella) - Lixiang Wei; Yanhan Bai; Rishen Liang; Junyan Lin; Minxuan Yang; Ying Tang; Hong Chen; Minshan Yao; Yao Huang; Li Lin; Zhendong Qin (Aquaculture, 2023)

The root-associated Fusarium isolated based on fungal community analysis improves phytoremediation efficiency of Ricinus communis L. in multi metal-contaminated soils - Huaxiong Yao; Wenguang Shi; Xing Wang; Junyan Li; Meiqi Chen; Jianbin Li; Danting Chen; Lin Zhou; Zujun Deng (Chemosphere, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Lifetime exposure to benzophenone-3 at an environmentally relevant concentration leads to female–biased social behavior and cognition deficits in zebrafish - Chenglian Bai; Haojia Dong; Junyan Tao; Yuanhong Chen; Hui Xu; Jian Lin; Changjiang Huang; Qiaoxiang Dong (Science of The Total Environment, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Approaches for the generation of active papain-like cysteine proteases from inclusion bodies of Escherichia coli - Chunfang Ling; Junyan Zhang; Deqiu Lin; Ailin Tao (World Journal of Microbiology and Biotechnology, 2015)